(untitled) (IMC Journal of Medical Science, 2021)
Background and objectives: Various new manifestations and risk factors for COVID-19 have been unveiled in the course of the current pandemic. Understanding the clinical spectrums as well as the risk factors associated with the adverse outcome of the disease is critical to combat this pandemic. This study was conducted to identify the clinical features, overall outcome and the factors associated with adverse outcome of the hospitalised COVID-19 patients in a semi-urban healthcare setting. Methods: This study was conducted at Debidwar Upazila (sub-district) Health Complex under the Cumilla district from April 2020 to October 2020. Reverse transcriptase-polymerase chain reaction (RT-PCR) positive COVID-19 patients, aged 18 years and above, admitted at the Health Complex were enrolled in the study. All patients were followed till their recovery, referral or death. The data were collected in a pre-designed semi-structured questionnaire that included demographic, epidemiological, clinical and laboratory parameters. Result: Out of 50 RT-PCR positiveCOVID-19 adult participants, 30 (60%) were males and 20 (40%) were females. Twenty-four percent, 36%, and 40% of the patients had mild, moderate and severe disease respectively. The most common clinical symptom was fever (96%), followed by cough (86%) and shortness of breath (60%). Hypertension (54%), diabetes mellitus (40%), bronchial asthma (20%) and chronic obstructive pulmonary disease (COPD, 14%) were the major co-morbid conditions. Of the total cases, 2 (4%) died and 8 (16%) required referral to tertiary care hospital while 40 (80%) recovered. COPD was associated with poor outcome (OR 19; 95% CI: 2.88, 125.31; p < 0.05). Smokers were 7 times more likely to exhibit the negative outcome than non-smokers (95% CI: 1.52, 32.33; p < 0.05). Conclusion: In this study, COPD was associated with a negative outcome. Further study with larger sample should be carried out to determine the spectrum of risk factors. Ibrahim Med. Coll. J. 2020; 14(2): 42-54